The effect of morphine on regional cerebral blood flow measured by 99mTc-ECD SPECT in dogs. - Antita Adriaens; Kathelijne Peremans; Tim Waelbers; Eva Vandermeulen; Siska Croubels; Luc Duchateau; André Dobbeleir; Kurt Audenaert; Jos Eersels; Simon Vermeire; Bart De Spiegeleer; Ingeborgh Polis (PLoS ONE, 2014)
To gain insights into the working mechanism of morphine, regional cerebral blood flow (rCBF) patterns after morphine administration were assessed in dogs. In a randomized cross-over experimental study, rCBF was estimated with 99mTc-Ethylcysteinate Dimer single photon emission computed tomography in 8 dogs at baseline, at 30 minutes and at 120 minutes after a single bolus of morphine. Perfusion indices (PI) in the frontal, parietal, temporal and occipital cortex and in the subcortical and cerebellar region were calculated. PI was significantly decreased 30 min after morphine compared to baseline in the right frontal cortex. The left parietal cortex and subcortical region showed a significantly increased PI 30 min after morphine compared to baseline. No significant differences were noted for the other regions or at other time points. In conclusion, a single bolus of morphine generated a changing rCBF pattern at different time points.